Actinic Cheilitis — From Risk Factors to Therapy - Vasilovici, Alina; Ungureanu, Loredana; Grigore, Lavinia; Cojocaru, Elena; Şenilă, Simona (Frontiers in Medicine, 2022)
Actinic cheilitis or solar cheilosis is considered a precursor of malignancy or even an in situ squamous cell carcinoma (SCC) of the lip, located most frequently on the lower lip. Actinic cheilitis (AC) has a higher likelihood of developing into invasive SCC of the lip, which is one of the deadliest non-melanoma skin cancers. Risk factors include chronic UV exposure, increasing age, male gender, fair phototypes, chronic scarring, immunosuppressive therapy, and tobacco use. From a clinical point of view, AC is characterized by dryness, scaling, atrophy, indistinct borders, and erosions. Ulceration and the appearance of a nodule often suggest the progression to invasive SCC. Dermoscopic examination reveals white structureless areas, scales, erosions, and white halos of the vermilion. Reflectance confocal microscopy shows disruption of the stratum corneum, parakeratosis, an atypical honeycomb pattern, solar elastosis, and dilated and tortuous blood vessels with increased blood flow. The rate of malignant transformation ranges from 10 to 30% and early diagnoses and treatment are essential in preventing the development of invasive SCC. Optimal treatment has not been established yet, but invasive and topical treatments can be tried. The present paper aims to review the existing data regarding epidemiology, risk factors, clinical picture, non-invasive imaging, diagnosis, and therapy in AC.